Application of Color Doppler Ultrasound in Microscopic Imaging Diagnosis of Adenomyosis. (31st May 2022) - Zhu, Jianchang; Liu, Shuang; Gao, Dandan
Abstract : In order to explore the value of color Doppler ultrasonography (TVCDS) in the diagnosis and differential diagnosis of adenomyosis. A total of 150 patients with adenomyosis admitted to a hospital from January 2020 to December 2021 were selected, taking transvaginal three-dimensional color Doppler ultrasound and abdominal ultrasound for examination, all results were compared with patient pathology or surgical results, in order to compare the accuracy of the two inspection methods. The positive predictive value of three-dimensional color Doppler ultrasonography was higher than that of abdominal ultrasonography, and the difference was statistically significant (P < 0.05 ). The coincidence rate, sensitivity, and specificity of three-dimensional color Doppler ultrasonography were higher than those of abdominal ultrasonography, while the misdiagnosis rate was lower than that of abdominal ultrasonography, and the differences were statistically significant (all P < 0.05 ). The imaging features of vaginal three-dimensional color Doppler ultrasound in patients with adenomyosis are mainly enlarged uterus, slightly stronger echoes in the myometrium with enhanced echogenic spots, and short or short branch blood flow signals in the lesions. After statistical analysis, there was a significant difference in the blood flow changes between benign and malignant endometrial echoes and abnormal echoes in the uterine cavity, P < 0.05 . Normal endometrium and benign intrauterine lesions mainly showed no blood flow signal, while malignant lesions in the uterine cavity mostly showed changes in blood flow signal. Compared with abdominal examination, transvaginal color Doppler ultrasonography has obvious advantages in the diagnosis of adenomyosis. According to the characteristics of ultrasound images, blood flow distribution, frequency spectrum, etc., it can provide a more accurate basis for clinical timely, provide the identification points of uterine fibroids, and provide help for clinicians to choose a treatment plan.